2000
DOI: 10.1111/j.1532-5415.2000.tb04784.x
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Assistants Detect Behavior Changes in Nursing Home Residents that Precede Acute Illness: Development and Validation of an Illness Warning Instrument

Abstract: A new instrument developed for nursing assistants to document behavioral and functional status changes in nursing home residents demonstrates fair sensitivity and high specificity for acute illness. Close monitoring of patients with a positive instrument might avert morbidity and mortality from acute illness by allowing earlier treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
56
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 23 publications
(21 reference statements)
3
56
0
1
Order By: Relevance
“…[14][15][16] Guidelines, care paths, and other tools for assessing changes in condition and for the most common conditions associated with hospital readmissions, including heart failure, pneumonia, renal failure/dehydration, and urinary tract infections, as well as strategies to enhance advance care planning, are available. [17][18][19][20][21][22][23][24][25][26][27] Although implementing clinical practice changes in the NH setting is challenging for many reasons, 20,28-31 use of some of these guidelines and tools has been associated with reduced hospitalizations in the NH population. [32][33][34][35] A CMS pilot study demonstrated a 50% reduction in hospitalizations in 3 NHs in Georgia with high hospitalization rates associated with a set of clinical practice tools that includes many of those mentioned previously (Interventions to Reduce Acute Care Transfers or ''INTERACT'').…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16] Guidelines, care paths, and other tools for assessing changes in condition and for the most common conditions associated with hospital readmissions, including heart failure, pneumonia, renal failure/dehydration, and urinary tract infections, as well as strategies to enhance advance care planning, are available. [17][18][19][20][21][22][23][24][25][26][27] Although implementing clinical practice changes in the NH setting is challenging for many reasons, 20,28-31 use of some of these guidelines and tools has been associated with reduced hospitalizations in the NH population. [32][33][34][35] A CMS pilot study demonstrated a 50% reduction in hospitalizations in 3 NHs in Georgia with high hospitalization rates associated with a set of clinical practice tools that includes many of those mentioned previously (Interventions to Reduce Acute Care Transfers or ''INTERACT'').…”
Section: Discussionmentioning
confidence: 99%
“…An additional strategy for reducing avoidable hospitalizations is the use of practice guidelines, care paths, communication, and other tools that assist NH health professionals in recognizing, reporting, and managing conditions, which may be helpful in bolstering NHs' ability to manage sicker residents. [30][31][32][33][34][35][36] For example, in a randomized trial conducted in several Canadian NHs, implementation of a care path for pneumonia with the support of a trained nurse was shown to be effective in reducing hospitalizations and related costs without greater mortality. 36 Similar tools were created as part of the larger CMS project at the Georgia QIO and are available on-line.…”
mentioning
confidence: 99%
“…These atypical signs are observed as absence of fever, weakness, falling, weight loss, physical dysfunction and cognitive decline [3,7,[12][13][14]. In addition, early signs of infection are very similar to, and also as diffuse as, signs of acute illness [12,15,16]. Changes, such as lethargy, weakness, decreased appetite, agitation, disorientation, dizziness, falls and delusions are reported to have high predictive values for acute illness in frail elderly [16].…”
mentioning
confidence: 91%